Relationship between perceived organizational support and organizational citizenship behaviour of academic staff at selected faculty in a Malaysian public research university - Hassan, Roshafiza; Basri, Ramli; Asimiran, Soaib; Omar, Zoharah (Faculty of Agriculture and Food Sciences, Universiti Putra Malaysia Bintulu Sarawak Campus, 2019)
This is a preliminary study to reports the findings on the relationship between Organizational Citizenship Behaviour (OCB) and perceived organizational support of academic staff at selected faculty in Malaysian Public Research University (RU). The objective is also to identify the relationships between perceived organizational support with five dimensions of OCB namely altruism, courtesy, civic virtue, conscientiousness and sportsmanship. An instrument using a 7-point scale and consisting of 32 items was used to measure the perception of academic staff on the perceived organizational support and the organizational citizenship behaviour at the institution. Findings of the study indicate that the mean score of academic staff perceived organizational support is 5.36 and a standard deviation of 1.000, which is lower as compared to the score on the academic staffs’ citizenship behaviour towards the organization, which obtained a mean of 5.83 and a standard deviation of .615. This study also reported that perceived organizational support has a significant impact on organizational citizenship behaviour (r = .309, p < .05) which explains 9.55 percent of the variance in academic staffs’ citizenship behaviour towards their organization. The finding also exhibits the perceived organizational support has a direct effect on the dimension of altruism and sportsmanship.